Prevalence and age of onset of Parkinson's disease in Cardiff: a community based cross sectional study and meta-analysis. - Wickremaratchi, M; Perera, D; O'Loghlen, C; Sastry, D; Morgan, E; Jones, A; Edwards, P; Robertson, N; Butler, C; Morris, H; Ben-Shlomo, Y (2009)
BACKGROUND: Previous prevalence studies of Parkinson's disease (PD) in the UK have spanned a 40 year period and have predominantly been in the North of the country. These have presented rates by current age but have not examined this by age at disease onset. METHODS: A community based prevalence study was undertaken which attempted to identify all clinically diagnosed cases of PD from primary and secondary care for the city of Cardiff, Wales, UK. A meta-analysis of all past studies in the UK, including our own, was also undertaken. RESULTS: Overall, 380 cases of PD were identified from a population of 292 637 residents, giving a crude prevalence rate of 130 per 100 000 (95% CI 117 to 144) and an age standardised rate of 142 per 100 000 (95% CI 128 156), standardised to the 1997 England and Wales population. Our prevalence rates were very similar to the weighted average of previous UK studies although there was evidence of between study heterogeneity (p = 0.0006). 5.4% and 31.2% of prevalent PD patients had their disease onset below the age of 50 or 65 years, respectively. CONCLUSIONS: The data suggest that there are no major geographical variations in the prevalence of PD in the UK and that the age adjusted prevalence rate has remained relatively stable over the past 40 years. Although PD risk is far greater in older subjects, patients with young onset are not that uncommon in the community, and health and social care provision should reflect their needs.